2019
DOI: 10.4067/s0718-381x2019000100046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Dental Caries and Fluorosis in 8 Year-old Children With or Without Fluoride Supplementation

Abstract: One of the most effective and studied measures in the prevention of caries is the use of fluoride, which has the property to reduce their incidence and severity. In Chile, 75 % of the population receives it the drinking water. In 1984, WHO recommended the use of milk as an alternative vehicle. In Chile, the Fluoridated School Feeding Program (FSFP) was introduced in 1994, using this alternative in rural areas without fluoride in water. The objective of the study was to compare prevalence and severity of dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The use of fluoridated milk as a community level intervention has been reported in some rural areas of Chile. 17 However, targeting culturally appropriate, economically sustainable caries control interventions to rural populations and native ethnic groups such as indigenous people (> 45 million and over 800 ethnic groups), quilombolas (African-origin), and riverside Amazonian people remains a crucial challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of fluoridated milk as a community level intervention has been reported in some rural areas of Chile. 17 However, targeting culturally appropriate, economically sustainable caries control interventions to rural populations and native ethnic groups such as indigenous people (> 45 million and over 800 ethnic groups), quilombolas (African-origin), and riverside Amazonian people remains a crucial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining relevant studies included in this report focused on the use of fluoride varnishes in Brazil, 36 Chile, 37 Dominican Republic, 38 and El Salvador, 39 and on the use of a combination of fluoride mouth-rinses and APF gels in Brazil 18,35 and Peru 30 . Some publications were more comprehensive and documented several strategies for fluoride use within the same country, such as in Chile, 17 Cuba, 16 Brazil, 18 Colombia, 29 Haiti, 19 and Peru, 30 or reported one or more strategies adopted in several LACC. 20,26,27 The remaining studies reported one specific strategy adopted in a single Latin American and Caribbean country.…”
Section: Venezuelamentioning
confidence: 99%
“…La prevalencia de fluorosis dental (FD) en Chile, es significativamente mayor en las comunidades con agua fluorada; y aunque el rol de los fluoruros en la prevención de caries es indiscutido e inocuo usado en la justa medida, las secuelas de su consumo excesivo se verifican principalmente en niños y jóvenes (1) .…”
Section: Introductionunclassified